Associations between cardiovascular risk factors and psoriasis in Iran - Farshchian M; Ansar A; Sobhan M (Dove Medical Press, 2015)
Mahmoud Farshchian, Akram Ansar, Mohammadreza Sobhan Psoriasis Research Center, Department of Dermatology, Farshchian Hospital, Hamadan University of Medical Sciences, Hamadan, Iran Background: Psoriasis is a common chronic inflammatory skin disease. There is overwhelming evidence on the higher risk of cardiovascular diseases in patients with psoriasis as a result of hyperlipidemia, which is more common in these patients. Objectives: The aim of this study was to elucidate the association between the cardiovascular risk factors and psoriasis. Methods: In a cross-sectional study, 55 patients with psoriasis and 55 matched (sex and age) controls were entered the study at the Department of Dermatology between March 2011 and March 2013. Blood samples were obtained following 14 hours fasting status and serum levels of triglyceride, cholesterol, high-density lipoprotein, and low-density lipoprotein were determined using standard laboratory methods, and other variables such as sex, age, smoking, alcohol consumption, and the type of disease were recorded. Results: Our findings showed that levels of triglyceride, low-density lipoprotein, and smoking were significantly higher in psoriatic patients when compared with controls, whereas the level of high-density lipoprotein and cholesterol was not significantly different between two groups. Body mass index of psoriatic patients was not significantly higher than controls. Patients with psoriasis also had an increased prevalence of hypertension. Conclusion: Our findings further verify lipid abnormalities in psoriatic patients. Psoriasis is associated with higher rate of hypertension, which may be resulted in increasing the risk of cardiovascular diseases in these patients. Thus, serum lipid profile and blood pressure in all patients with psoriasis, regardless of disease severity, deserve consideration to be checked. Keywords: cardiovascular disease, risk factors, psoriasis, lipid profile